2000
DOI: 10.1037/0278-7393.26.5.1103
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition effects in adult lexical processing reflect loss of plasticity in maturing systems: Insights from connectionist networks.

Abstract: Early learned words are recognized and produced faster than later learned words. The authors showed that such age of acquisition effects are a natural property of connectionist models trained by backpropagation when patterns are introduced at different points into training and learning of early and late patterns is cumulative and interleaved. Analysis of hidden unit activations indicated that the age of acquisition effect reflects a gradual reduction in network plasticity and a consequent failure to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
518
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(572 citation statements)
references
References 44 publications
47
518
7
Order By: Relevance
“…Its logic is as follows: A memory network organizes itself, through larger weight changes, into a certain efficient configuration early on to represent what it knows about (e.g., a childhood language); it cannot nimbly reorganize itself even if the nature of the input changes (e.g., a second language). Thus early-learned materials will have an advantage and lasting impact on the memory network (e.g., Ellis & Lambon-Ralph, 2000;Zevin & Seidenberg, 2004). While our study was not set up to evaluate this account, our findings nonetheless need to be reckoned with.…”
Section: Discussionmentioning
confidence: 85%
“…Its logic is as follows: A memory network organizes itself, through larger weight changes, into a certain efficient configuration early on to represent what it knows about (e.g., a childhood language); it cannot nimbly reorganize itself even if the nature of the input changes (e.g., a second language). Thus early-learned materials will have an advantage and lasting impact on the memory network (e.g., Ellis & Lambon-Ralph, 2000;Zevin & Seidenberg, 2004). While our study was not set up to evaluate this account, our findings nonetheless need to be reckoned with.…”
Section: Discussionmentioning
confidence: 85%
“…When it is time to acquire the more difficult What task, however, it turns out to be impossible to reach perfect performance in the later acquired What task. Many simulations using the backpropagation algorithm have shown that neural networks exhibit what is sometimes called the "age of acquisition" effect: at the end of the simulation performance on tasks that are learned earlier than other tasks is better than performance on later acquired tasks (Ellis & Lambon Ralph, 2000;Smith et al, in press). This "age of acquisition" effect is observed also in our simulations in which populations of neural networks evolve the ability to solve the What and Where tasks, as can be seen by plotting separately the fitness curves for the Where and the What tasks in the modular architecture ( Figure 7).…”
Section: Figure 5 Average Fitness (Error) Across 50000 Generations mentioning
confidence: 99%
“…The financial support of the Italian National Research Council (Short Term Mobility Program 2000 to RC and Bilateral Project 1998-2000 and by the Yale Institute for Biospheric Studies to GPW is gratefully acknowledged. The authors thank the referees for valuable suggestions on the manuscript.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[41,42]). These models allow researchers complete control over simulated learning systems and their environments, to help identify factors contributing to enhanced learning during particular points in development.…”
Section: Learning Across Developmentmentioning
confidence: 99%
“…Such simulations have demonstrated that entrenchment can occur as some units and connections become committed and unused connections are pruned [41,42]. The result is that stimuli encountered early are learned more robustly than stimuli encountered later.…”
Section: Learning Across Developmentmentioning
confidence: 99%